The Children's Table : Childhood Studies and the Humanities - Duane, Anna Mae, 1968- (Book collections on Project MUSE., 2013)
This collection brings together an eclectic range of prominent scholars in architecture, education, history, law, literary criticism, and cultural studies to explore how the field of childhood studies questions some of the most basic tenets of humanities scholarship - and to consider how these questions can bridge disciplines. Each essay pairs childhood studies with another field of inquiry to ask explicitly how foregrounding the child reorients long-established scholarly foundations in that field. Childhood studies' insistence that we need to rethink the symbolic work of the child necessarily realigns a host of other fields that, often uncritically, draw upon the false dichotomy separating the vulnerable, dependent child from the allegedly independent and autonomous adult. By complicating our assumptions about the child, we are also providing a new way of thinking through some of the most basic tenets of the humanities. The editor of the collection notes that much of the exciting work in the humanities seeks to recover the voices of those who have been infantilized, including women, people of color, and the LGBT community. This volume features thirteen essays by leading scholars who reveal how childhood studies offers a vital methodological and theoretical roadmap for engaging issues that are among the most important and provocative in the humanities - the recovery of colonized voices, the definition of agency, the performance of identity, and the construction of gender and race, to name a few. Each of the essays seeks to understand how rhetorical views of childhood shape views of power, politics, knowledge, and sociality. --